Studi Analisis tentang Kelimpahan Damai Sejahtera dalam Surat Filipi 4:4-9 - Eni Lestari (Predica Verbum: Jurnal Teologi dan Misi, 2021)
The letter that was sent by Paul to the Philipians contains important messages that are precisely accurate to be implemented in the life of believers nowadays. The condition of the world that doesn’t provide any assurance of security, moreover with the pandemic issue which is still happening, become the most factors of the absence of peace. The government is not capable enough to guarantee the tranquility, but Paul consoles the heart of believers, to remind them that they have the double nationality, both earth and heaven. If the world doesn’t offer and assure a sense of safety, then there is heaven, the one they can yearn to. This trust confirmed with concition that, “God is near” (Phil. 4:5). This article is going to discuss practical steps on how to enjoy a peaceful prosperous by analyzing each and every words in Philipians 4:4-9. Choosing important sentence parts in Greek, translating based on the rules, and finding the intended meaning will be the main activities in this research. At the end of the exploration process, the writer will present the results of the discovery of the valuable truth for today's life in practical and meaningful writing.